Just Interested or Getting Involved? An Analysis of Superannuation Attitudes and Actions1. Issue 289 (18th March 2014) - Bateman, Hazel; Deetlefs, Jeanette; Dobrescu, Loretti I.; Newell, Ben R.; Ortmann, Andreas; Thorp, Susan
<x xml:space="preserve">Abstract</x> Low levels of non‐default decision‐making among superannuation members in Australia are assumed to be evidence of a lack of interest and capability. Using member records and survey data from a large Australian superannuation fund, we test the relationship between attitudes towards retirement savings and observable levels of non‐default activities (such as making voluntary contributions, choosing or changing investment options and changing insurance cover). Additional retirement savings contributions by permanent staff are more likely if the staff member is very likely to recommend their superannuation fund. Individuals who rate their own personal interest in superannuation affairs as very high are more likely to be active online. This, however, does not extend to choosing a non‐default investment or purchasing additional insurance, where we find no differences between the highly interested and the disengaged. These findings, together with several other differences related to demographics and employment conditions, show that non‐default activity is not a reliable proxy for member engagement.